Sistem Absensi Kepegawaian Pada Dinas Perikanan Kabupaten Karawang - Muhamad Yogi Septian; Puji Isyanto; Dini Yani (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine a staff attendance system at the Karawang District Fisheries Service. The attendance system at the fisheries service uses the fingerpint attendance that is currently in use, with the aim of increasing efficiency and accuracy in managing employee attendance data, as well as improving work performance and discipline. The practical work method used is the observative method. type of research that aims to describe or describe existing phenomena. The results of this study are to determine the attendance system and the development of an information technology-based attendance system that includes the use of hardware and software. This system is designed to make it easier for employees to record their attendance accurately and efficiently. The hardware used in this system includes an attendance machine with fingerprint recognition features and employee identification cards. The developed software has a user-friendly interface, enabling employees to register themselves, record daily attendance and view their attendance reports. Implementation of this system is carried out by installing hardware at the employee's work location and integrating it with software that is connected to a central database. After implementation, the system is tested and evaluated to ensure its performance is as expected. The results of this study indicate that the use of this employee attendance system can improve efficiency and accuracy in managing attendance data. With the use of information technology, the process of recording employee attendance can be done quickly and easily. This system also provides convenience in producing accurate and detailed attendance reports and can improve employee performance and discipline.